Resilience of breadfruit agro-ecosystems in Hawaiʻi during the COVID-19 pandemic - E. H. Berning; C. V. H. Andersen; O. Mertz; N. Dickinson; M. Opgenorth; N. K. Lincoln; J. H. Rashford; N. Rønsted (CABI Agriculture and Bioscience)
Abstract Background The COVID-19 pandemic is interrupting domestic and global food supply chains resulting in reduced access to healthy diverse diets. Hawaiʻi has been described as a model social-ecological system and it has been suggested that indigenous agro-ecosystems have the potential to be highly productive and resilient under changing land-use and climate change disturbance. However, little research has yet been conducted exploring the disruption and resilience of agro-ecosystems in Hawaiʻi caused by the COVID-19 pandemic. The breadfruit tree (Artocarpus altilis; Moraceae) is a signature, multi-purpose-tree of the complex perennial agro-ecosystems systems in Oceania. Methods This case study explores the ways in which the breadfruit agro-ecosystems of Hawaiʻi have shown resilience during the COVID-19 pandemic. Results Our study suggests that breadfruit has increased its value as a subsistence crop during the COVID-19 pandemic, even in a developed economy like Hawaiʻi, and that resilience of Hawaiian breadfruit agroe-cosystems during a crisis can be supported through cooperatives and food-hubs.